Management of Weekly Group Meetings and Workload as Determinants of Administrative Officer Turnover: an Analysis of The Collaborative Role of Group Leaders at PT PNM Tangerang - Irma Damayanti (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This study examines the influence of Weekly Group Meeting Governance (PKM Governance) and workload on Account Officer (AO) turnover at PT Permodalan Nasional Madani, Tangerang Branch, with group leader collaboration acting as a moderating variable. The research was motivated by the increasing turnover rate of AOs despite improved customer attendance in weekly group meetings, indicating a gap between operational performance and employee retention. A quantitative approach was employed using survey methods and questionnaires distributed to 285 respondents, selected through simple random sampling from a population of 989 employees. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings reveal that PKM Governance has a significant negative effect on AO turnover, indicating that better management of weekly group meetings reduces employees’ intention to leave the organization. Conversely, workload has a significant positive effect on turnover, demonstrating that excessive work demands increase stress, fatigue, and turnover intention. Furthermore, group leader collaboration was found to significantly moderate the relationship between workload and turnover by weakening the negative impact of high workload on employee retention. However, group leader collaboration did not significantly moderate the relationship between PKM Governance and turnover. The study highlights the importance of balanced workload management, structured operational governance, and collaborative leadership in reducing employee turnover within the microfinance sector. These findings contribute to the integration of operational governance and organizational behavior perspectives in understanding turnover dynamics among Account Officers in community-based microfinance institutions.